La fatale congiunzione. Mondi salienti e formazioni di compromesso - de Cristofaro, Francesco (Status Quaestionis, 2013)
This essay originates from a variation of Manzoni’s Fermo e Lucia (a later to be deleted phrase presenting a “short-circuit” through a figure of speech, or maybe a lapsus) and a paratextual passage from the 1830’s Ivanhoe. The essay analyses the complex relationship between “fortuna” and “provvidenza” in The Betrothed, the novelistic masterpiece by Manzoni, paying special attention to the chapters in which the grip of fate seems to be stronger (e.g. the chapters about the plague). Drawing from both Kohler’s and Jameson’s theories of the secularization of providence, this essay scrutinizes the plot of coincidences of The Betrothed, while providing the foundations of a theoretical discussion.